Changes in flowering functional group affect responses of community phenological sequences to temperature change. Issue 3 (10th February 2017) - Meng, F. D.; Jiang, L. L.; Zhang, Z. H.; Cui, S. J.; Duan, J. C.; Wang, S. P.; Luo, C. Y.; Wang, Q.; Zhou, Y.; Li, X. E.; Zhang, L. R.; Li, B. W.; et al.
Abstract: Our ability to predict how temperature modifies phenology at the community scale is limited by our lack of understanding of responses by functional groups of flowering plants. These responses differ among species with different life histories. We performed a reciprocal transplant experiment along four elevation gradients (e.g., 3, 200, 3, 400, 3, 600 and 3, 800 m) to investigate the effects of warming (transferred downward) and cooling (transferred upward) on plant flowering functional groups (FFGs) and community phenological sequences (i.e., seven phenological events). Warming significantly decreased early‐spring‐flowering (ESF) plant coverage and increased mid‐summer‐flowering plant (MSF) coverage, while cooling had the opposite effect. All community phenological events were advanced by warming and delayed by cooling except for the date of complete leaf‐coloring, which showed the opposite response. Warming and cooling could cause greater advance or delay in early‐season phenological events of the community through increased coverage of MSF species, and warming could delay late‐season phenological events of the community by increased coverage of ESF species. These results suggested that coverage change of FFGs in the community induced by temperature change could mediate the responses of the community phenological events to temperature change in the future. The response of phenological events to temperature change at the species level may not be sufficient to predict phenological responses at the community‐level due to phenological compensation between species in the community.